2016
DOI: 10.1093/aje/kwv195
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Consumption of Seafood in Pregnancy and Child Neuropsychological Development: A Longitudinal Study Based on a Population With High Consumption Levels

Abstract: Seafood consumption during pregnancy is thought to be beneficial for child neuropsychological development, but to our knowledge no large cohort studies with high fatty fish consumption have analyzed the association by seafood subtype. We evaluated 1,892 and 1,589 mother-child pairs at the ages of 14 months and 5 years, respectively, in a population-based Spanish birth cohort established during 2004-2008. Bayley and McCarthy scales and the Childhood Asperger Syndrome Test were used to assess neuropsychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
81
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 25 publications
(42 reference statements)
2
81
0
4
Order By: Relevance
“…Of 20 previous studies using the BSID (Davidson et al 1995(Davidson et al , 2008Jedrychowski et al 2006Jedrychowski et al , 2007Lederman et al 2008;Plusquellec et al 2010;Stokes-Riner et al 2011;Llop et al 2012;Watson et al 2012;Valent et al 2013;Boucher et al 2014;Hsi et al 2014;Strain et al 2015;Marques et al 2015Marques et al , 2016aRothenberg et al 2016;Julvez et al 2016;Prpić et al 2017), 11 reported adverse effects of methylmercury on the PDI, and three observed such effects on the MDI; that is, these rates of 11/20 and 3/20 differed significantly (Fisher exact test, P = 0.019). Thus, psychomotor development appeared to be more susceptible to methylmercury than mental development.…”
Section: Discussionmentioning
confidence: 87%
“…Of 20 previous studies using the BSID (Davidson et al 1995(Davidson et al , 2008Jedrychowski et al 2006Jedrychowski et al , 2007Lederman et al 2008;Plusquellec et al 2010;Stokes-Riner et al 2011;Llop et al 2012;Watson et al 2012;Valent et al 2013;Boucher et al 2014;Hsi et al 2014;Strain et al 2015;Marques et al 2015Marques et al , 2016aRothenberg et al 2016;Julvez et al 2016;Prpić et al 2017), 11 reported adverse effects of methylmercury on the PDI, and three observed such effects on the MDI; that is, these rates of 11/20 and 3/20 differed significantly (Fisher exact test, P = 0.019). Thus, psychomotor development appeared to be more susceptible to methylmercury than mental development.…”
Section: Discussionmentioning
confidence: 87%
“…PUFAs play pivotal roles in infant neurodevelopment [5, 6]. In particular, LA and ALA are regarded as nutritionally essential fatty acids because they cannot be synthesized de novo from macronutrients [3] and can also convert into AA and DHA, respectively [23].…”
Section: Discussionmentioning
confidence: 99%
“…Other cohort studies from England, Spain, and Japan showed that maternal seafood and fish consumption as a proxy for LC-PUFAs was associated with neuropsychological test scores in children [5, 6, 28, 29]. The dietary n-3 LC-PUFAs including ALA, are found mainly in marine products like seaweed and fish.…”
Section: Discussionmentioning
confidence: 99%
“…Fish consumption is considered as surrogate for omega-3 fatty acid consumption, which associates with cognitive outcomes in pregnant women 88,89 . Children from mothers with no seafood consumption were at greatest risk of adverse or suboptimal verbal IQ.…”
Section: *N/a: Not Availablementioning
confidence: 99%